La Comprensión Del Cuerpo Humano En El Pensamiento De Francisco De Asís, Según Sus Escritos: Análisis Lexical - Quesada Navarro, Marcos Alejandro (Miscellanea francescana, 2025)
Although Francis of Assisi cannot be regarded as a professional writer, but rather a circumstantial one, driven by necessity, his writings, despite their lack of systematicity, reveal a linguistically cohesive and inherently convergent code. This lexical coherence serves as a privileged key to gaining a deeper understanding of his thought, especially when his texts are analyzed from a thematic perspective, as adopted in the present study. This paper focuses on the concept of the human body that emerges from the writings of the Poverello, taking as its starting point a rigorous lexical analysis of the vast terminological repertoire associated with corporeality. This approach allows for the reassessment of numerous biased interpretations of Francis's vision of the body and, while concentrating on a specific aspect of his thought, contributes to a broader, more articulated, and precise understanding of his rich and captivating spiritual experience.